The Immunomodulatory Drug Glatiramer Acetate is Also an Effective Antimicrobial Agent that Kills Gram-negative Bacteria. Issue 1 (December 2017) - Christiansen, Stig; Murphy, Ronan; Juul-Madsen, Kristian; Fredborg, Marlene; Hvam, Michael; Axelgaard, Esben; Skovdal, Sandra; Meyer, Rikke; Sørensen, Uffe; Möller, Arne; Nyengaard, Jens; Nørskov-Lauritsen, Niels; et al.
Abstract Classic drug development strategies have failed to meet the urgent clinical needs in treating infections with Gram-negative bacteria. Repurposing drugs can lead to timely availability of new antibiotics, accelerated by existing safety profiles. Glatiramer acetate (GA) is a widely used and safe formulation for treatment of multiple sclerosis. It contains a large diversity of essentially isomeric polypeptides with the cationic and amphiphilic character of many antimicrobial peptides (AMP). Here, we report that GA is antibacterial, targeting Gram-negative organisms with higher activity towardsPseudomonas aeruginosa than the naturally-occurring AMP LL-37 in human plasma. As judged from flow cytometric assays, bacterial killing by GA occurred within minutes. Laboratory strains ofEscherichia coli andP .aeruginosa were killed by a process of condensing intracellular contents. Efficient killing by GA was also demonstrated inAcinetobacter baumannii clinical isolates and approximately 50% of clinical isolates ofP .aeruginosa from chronic airway infection in CF patients. By contrast, the Gram-positiveStaphylococcus aureus cells appeared to be protected from GA by an increased formation of nm-scale particulates. Our data identify GA as an attractive drug repurposing candidate to treat infections with Gram-negative bacteria.